2019
DOI: 10.1002/uog.20118
|View full text |Cite
|
Sign up to set email alerts
|

Multivariable evaluation of maternal hemodynamic profile in pregnancy complicated by fetal growth restriction: prospective study

Abstract: In pregnancies complicated by intrauterine growth restriction and hypertensive disorders, intrauterine growth restriction has a significant independent effect on most maternal hemodynamic parameters, even after adjustment for major cardiovascular confounding factors. This article is protected by copyright. All rights reserved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 29 publications
1
16
0
Order By: Relevance
“…Statistical analysis was performed using Statistical Package for Social Sciences (SPSS) v. 22. The sample size estimation was based on a previous echocardiographic study, which reported a 10% lower maternal CO in normotensive women with FGR fetuses compared with women with appropriate‐for‐gestational‐age fetuses 27 . We calculated that the enrollment of 26 women either in the FGR and appropriate‐for‐gestational‐age group was needed to show a a 10% lower CO in the former group at 80% power and at a significance level of .05.…”
Section: Methodsmentioning
confidence: 99%
“…Statistical analysis was performed using Statistical Package for Social Sciences (SPSS) v. 22. The sample size estimation was based on a previous echocardiographic study, which reported a 10% lower maternal CO in normotensive women with FGR fetuses compared with women with appropriate‐for‐gestational‐age fetuses 27 . We calculated that the enrollment of 26 women either in the FGR and appropriate‐for‐gestational‐age group was needed to show a a 10% lower CO in the former group at 80% power and at a significance level of .05.…”
Section: Methodsmentioning
confidence: 99%
“…In an uncomplicated pregnancy, there is a positive correlation between CO change from preconception to mid-gestation and neonatal birth weight ( 18 ). During pregnancy from the first trimester onward, maternal CO is directly related to singleton birth weight ( 19 21 ), particularly at advanced maternal age ( 22 ), with parity ( 23 ), and multiple pregnancies ( 24 ), whereas there is an inverse relation with altitude ( 25 ) and gestational hypertensive disorders ( 26 , 27 ). Figure 1 shows the gestational trends of CO and TVR as measured by the bioimpedance technology: contrary to pregnancies eventually developing PE, the evolution is similar in FGR and uncomplicated pregnancy, however, at lower CO and higher TVR ( 10 , 11 , 28 ).…”
Section: Maternal Hemodynamics and Fetal Growthmentioning
confidence: 99%
“…Similarly, fewer than half of participants evaluated maternal hemodynamics in the presence of FGR. Pregnancies complicated by placental insufficiency are characterized by a specific maternal hemodynamic profile that appears to be more marked in the case of severe FGR 30 . Despite this emerging evidence, this evaluation is still not recommended nor it is widespread in the clinical setting.…”
Section: Discussionmentioning
confidence: 99%
“…30 Despite this emerging evidence, this evaluation is still not recommended nor it is widespread in the clinical setting. It is surprising that almost half of the participants gave a positive answer TA B L E 3…”
mentioning
confidence: 99%